1997
DOI: 10.1038/bjc.1997.191
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity at the 5,10-methylenetetrahydrofolate reductase locus in human ovarian carcinomas

Abstract: Summary The high-affinity folate-binding protein (FBP) is primarily involved in the uptake of the 5-methyltetrahydrofolate, and its expression may be physiologically regulated by the intracellular folate content. The overexpression of FBP on the cell surface of ovarian carcinoma cells may be responsible for an increased folate uptake. We tested the hypothesis of the existence of a defect in the 5, 10-methylenetetrahydrofolate reductase (MTHFR) in ovarian tumours that could cause reduced intracellular regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Hypermethylation of IGSF4 was described in cervical (Li et al, 2005) and pancreatic (Jansen et al, 2002) cancers. MTHFR had not been previously shown to be hypermethylated in ovarian cancers, but it had been linked to ovarian carcinogenesis by loss of heterozygosity (Viel et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of IGSF4 was described in cervical (Li et al, 2005) and pancreatic (Jansen et al, 2002) cancers. MTHFR had not been previously shown to be hypermethylated in ovarian cancers, but it had been linked to ovarian carcinogenesis by loss of heterozygosity (Viel et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that MTHFR undergoes 15 -20% LOH in colorectal tumours (Pereira et al, 1999); LOH for MTHFR may be as high as 45 -50% in ovarian tumours (Viel et al, 1997). Treatment of two neuroblastoma cell lines and two breast carcinoma cell lines showed significant decreases in cell survival after treatment with 400 nM of EX5 compared to control oligo treated cells.…”
Section: Sw620 Skbr3mentioning
confidence: 97%
“…The identification of a second polymorphism within the MTHFR gene i.e., 1298A fi C (E429A) (Viel et al 1997;van der Put et al 1998) and its apparent association with decreased enzyme activity (van der Put et al 1998;Weisberg et al 1998Weisberg et al , 2001) has led to several association studies investigating the MTHFR 1298A fi C polymorphism and NTDs. Results from these studies have been inconsistent and Yamada et al (2001) found no difference in enzyme activity of 1298A fi C variants.…”
Section: Introductionmentioning
confidence: 99%